Model-based multi-year P flow analyses and strategies for sustainable food chain management in Changzhou city at China's Taihu Basin - Guo, Zheng; Xu, Yunwei; Chen, Sophia Shuang; Kattel, Giri Raj (Frontiers in Sustainable Food Systems, 2025)
Cities, as a geographical unit with the greatest intensity of human socio-economic activities, have become the core nodes that disrupt the natural cycle of phosphorous (P) and regulate P flow toward sustainable development. However, P flows and its balance in many Chinese cities are largely unknown. This study employed the substance flow analysis (SFA) method to construct a P flow model for the food chain in Changzhou, a representative lakeside city in the Taihu Basin. From 2000 to 2021, the total P input and stock in Changzhou city's food chain system declined from 5,698.55 tP and 5,219.55 tP to 2,391.26 tP and 1,760.46 tP, respectively. Conversely, the total P loss surged from 478.99 tP to 630.79 tP, suggesting an open and unrestricted P flow. The P use efficiency (PUE) in animal production increased from 30.11% in 2000 to 37.65% in 2021, while that in crop production and the overall food chain increased from 51.41 and 65.74% in 2000 to 71.94% and 80.16% in 2021. Scenario analysis revealed that reducing food P uptake could lower total food chain P inputs and dependence on external P. Fertilizer recommendations could boost the PUE of crop production from 71.94% to 81.34%. Besides, urine diversion and waste incineration scenarios significantly decreased P accumulation in the food chain. Improving sewage treatment technology could further cut P discharge. An adaptive food chain P flow management framework was proposed. Leveraging the self-management and replicability of cities, this framework can be easily implemented in other regions and has the potential to be scaled up nationally, aiming to mitigate P loss and enhance P utilization efficiency.